Quality improvement work in general practice; a Norwegian focus group study - Torunn Bjerve Eide; Holgeir Skjeie; Sigurd Høye (Scandinavian Journal of Primary Health Care)
Background Quality improvement work is an essential feature of healthcare services, including general practice. In this study, we aimed to gain more knowledge regarding general practitioners’ (GPs) motivation for such work in their practices, as well as what kind of measures were considered motivating and feasible.Materials and methods We conducted five focus group interviews among Norwegian GPs between November 2021 and November 2022. We included 21 GPs of varying age, gender, experience, and geographic situation. The data were transcribed verbatim and analysed by Systematic Text Condensation, a thematic cross-case analysis.Results Many GPs had a diverse and imprecise understanding of the term quality improvement, and sound routines in everyday practice were often given as examples of quality improvement measures. There was a universal attitude that quality improvement initiatives should be close to practice, professionally relevant, and sufficiently small to be manageable. The availability of professional communities, either in the GP practices or in continuous medical education groups, was important for motivation. The role of nurses and health secretaries was highlighted as essential to achieve change. Participants commonly described negative reactions to programs that were imposed by external actors without regard for the GPs’ perceived needs.Conclusion GPs were motivated for quality improvement measures provided feasibility within the framework of general practice. Well-functioning professional communities, including involvement of nurses and health-secretaries, were emphasised as requisite for quality improvement. Small scale quality improvement programs suited for the needs of general practice were well received and should be further developed.